Tingkat kepadatan lalat dan identifikasi jenis lalat pada tempat penjualan ikan di Pasar Peunayong Kota Banda Aceh - Rahmayanti Rahmayanti; Erlinawati Erlinawati; Safwan Safwan (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: The presence of flies indicates a place's poor cleanliness. Fish is a food source of protein which is a human need. The presence of flies on fish indicates that the level of freshness and cleanliness is not good in a fish market. Of course, it was made worse by the large piles of garbage.Objective: The purpose of the study was to determine the density of flies and identify the types of flies at the fish selling point in Peunayong Market, Banda Aceh City.Method: This descriptive study used an experimental design by measuring the density of flies and identifying flies. The research was carried out at the Peunayong Market, Banda Aceh, in 2020. Snippets of using flies through the fly identification process at the Microbiology Laboratory of Aceh Health Polytechnic, Ministry of Health. The data collected is the density of flies using the fly grill method and catching flies using fly traps. Data analysis was carried out univariate, with frequency distribution and descriptive.Results: The results showed that the average fly density was 4.52 at the fish selling point in the Peunayong market, Banda Aceh, which was in the medium category. The types of flies in fish selling places at the Peunayong market in Banda Aceh are Musca domestica and Crysomya megachepala.Conclusion: The fly density level in the Peunayong fish market was in the medium category, and the most common fly found was the Crysomya megachepala.